The variability of the effect of pre-start warm-up on the activation of a swimmer's competitive performance - Marin I.S. ,; Golushko T.V. ,; Kolganova E.Yu. ,; Gridneva E.V. , (Theory and Practice of Physical Culture, 2025)
Objective of the study was to assess the efficacy of different warm-up techniques employed by swimmers in enhancing their athletic abilities. Methods and structure of the study. After examining the available literature in the Scopus and RSCI databases, a retrospective analysis was conducted on the approaches, content, and methodological frameworks for pre-swim warm-up in swimming, with a focus on the evolution of theory and methods in sports training. Results and conclusions. It was discovered that the ideal pre-swim warm-up for a swimmer involves a moderate initial activity of swimming at a distance of 1000 meters at a speed of 60-80% of their maximum oxygen consumption. To optimize performance in the short term, it is more beneficial to take a short rest period of 3-10 minutes. In this context, a longer or more intense warm-up can lead to an excessive activation of energy systems, potentially triggering various biomechanical and physiological responses, which can be both beneficial and detrimental, depending on the demands of the competition.